Modulation of cultured neural networks using neurotrophin release from hydrogel-coated microelectrode arrays - Jun, Sang Beom (2008)
Polyacrylamide and poly(ethylene glycol) diacrylate hydrogels were synthesized and characterized for use as drug-release and substrates for neuron cell culture. Protein release kinetics was determined by incorporating bovine serum albumin (BSA) into hydrogels during polymerization. To determine if hydrogel incorporation and release affects bioactivity, alkaline phosphatase was incorporated into hydrogels and released enzyme activity determined using the fluorescence-based ELF-97 assay. Hydrogels were then used to deliver brain derived neurotrophic factor (BDNF) from hydrogels polymerized over planar microelectrode arrays (MEA). Primary hippocampal neurons were cultured on both control and neurotrophin-containing hydrogel-coated MEAs. The effect of released BDNF on neurite length and process arborization was investigated using automated image analysis. Increased spontaneous activity as a response to released BDNF was recorded from the neurons cultured on top of hydrogel layers. These results demonstrate that proteins of biological interest can be incorporated into hydrogels to modulate development and function of cultured neural networks. These results also set the stage for development of hydrogel-coated neural prosthetic devices for local delivery of various biologically active molecules.